SUG‘ORILADIGAN VOHA LANDSHAFTLARNING DINAMIKASINI TADQIQ ETISH MASALALARI - Nazarov, M.G.; Sh.Poyanov, J. (SCIENCE and SOCIETY, 2024)
This article is a theoretical analysis of the dynamics of irrigated Oasis landscapes, which is considered one of the pressing issues of today. The main focus of the article is on the analysis of several points of the field of Science in the study of landscape dynamics.
Keywords: dynamics; landscape dynamics; anthropogenic dynamics; geosystem; invariant